EFFECTIVENESS OF ROSEMARY ESSENTIAL OIL AROMATHERAPY ON PAIN POST SECTION CAESAREA - jesica, fanny; Amir, Ade Nurhasanah; Anggarini, Marisa Lia (E-Jurnal Medika Udayana, 2025)
Fanny Jesica 1 , Ade Nurhasanah Amir 2 1,2 Study Program of Midwifery Profesion Education, Syedza Saintika University Corresponding email : fjesica89@gmail.com   AB STRACT   Background: Background: Caesarean section delivery is an alternative delivery, especially in complicated deliveries, but currently it is an option without indication chosen by mothers who give birth, so it can be seen that the number of SC deliveries is increasing. SC births in Indonesia have the highest incidence rate in DKI Jakarta at 31.3% and the lowest in Papua at 6.7%. 10 Meanwhile, based on the West Sumatra Provincial Health Service, the prevalence of cesarean section was 24.6% in 2020 and the prevalence for Padang City reached 23%. 4 Caesarean section delivery certainly has a higher impact than normal delivery. Post-SC pain is one of the discomforts felt by patients. One non-pharmacological method that can be applied to reduce post-SC pain is aromatherapy. Various flower extracts can be used for complementary therapy to suppress pain, including is rosemary essential oil. The research aims to see the effectiveness of giving rosemary aromatherapy on post-SC pain.Method: This type of quantitative research uses a quasi-experimental with one group pretest-posttest design. The population in this study was all Post Caesarean section patients at the Mentawai Islands Hospital in 2024 totaling 84 people and the sample used was 20 people. The sampling technique used consecutive sampling. The instrument used is the Numeric Rating Scale (NRS). Use rosemary essential oil by diffusion using a diffuser, at a dose of 5-10 drops diluted with 20 ml of water given over 2x60 minutes, given simultaneously after 24 hours Post-SC. Data analysis is presented univariate and bivariate by using the Wilcoxon test.Results: The average intensity of pain post-section Caesarea before being given rosemary essential oil aromatherapy with a mean of 8.70. The average intensity of pain post-section Caesarea before being given rosemary essential oil aromatherapy with a mean of 5.56 with a p-value 0.000Conclusion: The statistical test results obtained p-value = 0.000 (<0.05) which means there was a reduction in post-cesarean section pain after giving rosemary essential oil aromatherapy. Suggestion: We hope that health workers, especially midwives, can apply rosemary oil essential aromatherapy as a complementary therapy in reducing post-SC pain.  Keywords: Rosemary Essential Oil Aromatherapy, Pain, Post Caesarean section